(untitled) (Advances in Applied Biological Research, 2026)
Aconitum heterophyllum Wall. ex Royle is a critically endangered Himalayan medicinal herb extensively used in traditional medicine for its analgesic, antipyretic, and anti-inflammatory properties. The present study evaluated the species through morphological characterization, qualitative phytochemical screening, and GC– MS profiling of methanolic root extracts. Morphological observations confirmed diagnostic features such as paired tuberous roots, palmately lobed leaves, and racemose inflorescences, supporting species authentication. Preliminary phytochemical analysis revealed the presence of alkaloids, carbohydrates, lipids/ fatty acids, and phenolic compounds, whereas flavonoids and saponins were absent. GC–MS analysis identified ten major compounds, predominantly α-linolenic acid, palmitic acid, fatty acid esters, carbohydrate derivatives, and nitrogen-containing metabolites. The findings indicate a chemically diverse metabolite profile with potential antioxidant and anti-inflammatory significance. However, the study also recognizes the limitations of GC–MS in detecting thermolabile diterpenoid alkaloids characteristic of Aconitum species. Overall, the study establishes baseline pharmacognostic and chemical markers useful for authentication, quality evaluation, conservation planning, and future LC–MS/MS- based metabolomic investigations of this threatened Himalayan medicinal plant.